Preparation of Alkyl Halide as Intermediate Compound in Synthesis Cationic Surfactant Alkyl Trimethyl Ammonium Chloride - Asdani Muatika Sari; Ani Suryani; Puspa Dewi Lotulung; Silvester Tursiloadi (Research Center for Chemistry - LIPI, 2017)
Cationic surfactant alkyl trimethyl ammonium chloride was synthesized by quartenerisation of tertiary amines. Materials used in quartenerization are tertiary amine and alkyl halide. Alkyl halide is a hydrocarbon derivative in which one or more hydrogen is replaced with halogen. In this research, thionyl chloride is used as a reactant . Thionyl chloride (SOCl2) is often used because it is easier to make, the yield is greater and byproducts are volatile. Alkyl halide is synthesized from the reaction of hexadecyl alcohol with thionyl chloride (SOCl2) at a temperature of 80 ° C for 24 hours in a reflux reactor. This study managed to get hexadecyl chloride from the reaction hexadecyl alcohol and thionyl chloride. It can be seen from the results of FTIR, LC/MS and GC/MS